2005
DOI: 10.1002/cne.20734
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of freezing and passive aversive behaviors

Abstract: Cues that predict aversive outcomes often produce marked inhibitions of behavior known as freezing, but it is unknown exactly what neural pathways cause this inhibition. The amygdala and bed nucleus of the stria terminalis, along with their projections to the periaqueductal gray, are strongly implicated in freezing, but it is not known how these structures inhibit motor output. The median raphe nucleus (MRN), which contains a major population of serotonin neurons, has also been implicated in freezing, but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 90 publications
0
42
0
5
Order By: Relevance
“…As the RMTg gained recognition as a distinct structure (Jhou, 2005;Jhou and Gallagher, 2007;Jhou et al 2009a, b;Perrotti et al, 2005;Kaufling et al, 2009Kaufling et al, , 2010, its capacity to control the activity of midbrain DA neurons (Hong et al, 2011;Matsui and Williams, 2011;Lecca et al, 2011Lecca et al, , 2012Matsui et al, 2014) and the implications of this action in aversion (Jhou et al, 2009b), reward (Hong et al, 2011), and neurobiological responses to certain drugs of abuse (Matsui and Williams, 2011;Lecca et al, 2011Lecca et al, , 2012Jhou et al, 2013;Wasserman et al, 2013;Matsui et al, 2014) continue to concern investigators. Despite this wealth of interest, a fundamental behavior-locomotor activation-has been overlooked, yet we show here that modulation of RMTg activity has profound effects on locomotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the RMTg gained recognition as a distinct structure (Jhou, 2005;Jhou and Gallagher, 2007;Jhou et al 2009a, b;Perrotti et al, 2005;Kaufling et al, 2009Kaufling et al, , 2010, its capacity to control the activity of midbrain DA neurons (Hong et al, 2011;Matsui and Williams, 2011;Lecca et al, 2011Lecca et al, , 2012Matsui et al, 2014) and the implications of this action in aversion (Jhou et al, 2009b), reward (Hong et al, 2011), and neurobiological responses to certain drugs of abuse (Matsui and Williams, 2011;Lecca et al, 2011Lecca et al, , 2012Jhou et al, 2013;Wasserman et al, 2013;Matsui et al, 2014) continue to concern investigators. Despite this wealth of interest, a fundamental behavior-locomotor activation-has been overlooked, yet we show here that modulation of RMTg activity has profound effects on locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…The rostromedial tegmental nucleus (RMTg), a recently discovered structure located in the mesopontine tegmentum (Jhou, 2005;Jhou et al, 2009a, b;Kaufling et al, 2009), projects preferentially and strongly to (Jhou et al, 2009a, b, Balcita-Pedicino et al, 2011Bourdy et al, 2014) and thus is a strong inhibitor of (Hong et al, 2011;Lecca et al, 2011Lecca et al, , 2012Matsui and Williams, 2011;Matsui et al, 2014) dopamine neurons in the VTA and substantia nigra compacta (SNc). RMTg is implicated together with the VTA in behavioral responding to reward omission, aversive stimuli, feareliciting stimuli, and certain drugs of abuse (Jhou et al, 2009a(Jhou et al, , 2013Hong et al, 2011;Lecca et al, 2011Lecca et al, , 2012Matsui and Williams, 2011;Wasserman et al, 2013) and, more recently, with the SNc in motor skill and motor learning (Bourdy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3;Jhou, 2005;Ferreira et al, 2008;Jhou et al, 2009a,b), as well as a substantial topographically organized input from the LHb (Herkenham and Nauta, 1979;Araki et al, 1988;Kim, 2009). The structure now known as the RMTg was initially identified in studies examining Fos activation by psychostimulants (Scammell et al, 2000;Perrotti et al, 2005;Colussi-Mas et al, 2007;Kaufling et al, 2009;Jhou et al, 2009a,b).…”
Section: Topographical Position Of the Rmtgmentioning
confidence: 94%
“…Another strong argument for a major relay function of the RMTg is that the above-cited inhibitory effect of LHb stimulation on DA cells can similarly be observed in the substantia nigra, which receives even weaker direct inputs from the LHb than the VTA (present results; Araki et al, 1988) but is also densely innervated by the RMTg (Ferreira et al, 2008;Jhou et al, 2009a,b). It is noteworthy that aversive stimuli may be signaled to the RMTg not only by the LHb, but also directly or indirectly by several other structures implicated in distinct aspects of aversive responses and fear behavior (Jhou, 2005;Quirk and Sotress-Bayon, 2009). Thus, the RMTg receives direct inputs from the ventral periaqueductal gray, anterior cingulate cortex, lateral septum, and bed nucleus of the stria terminalis (Kaufling et al, 2009;Jhou et al, 2009b) and may receive indirect inputs from the central nucleus of the amygdala via the ventral periaqueductal gray.…”
Section: General Functional Commentsmentioning
confidence: 98%
“…Studies have shown that this sensory overresponsivity (SOR) is predicated on a hyperactivity in areas related to primary sensory processing, emotional regulation, and response to threat (Green et al 2015). 37 A similar, but less pronounced, inhibitory role is played by the freeze reflex, which seems to be driven by GABAergic and cholinergic neurotransmission (Power and McGaugh 2002;Jhou 2005). 38 Despite its reflexive nature TI is not easy to fit into the sympatheticparasympathetic dichotomy.…”
mentioning
confidence: 99%